STRUKTUR KOMUNITAS DAN DISTRIBUSI TEMPORAL GASTROPODA DI DANAU SITU GINTUNG, TANGERANG SELATAN, BANTEN - Yayan Mardiansyah Assuyuti; Alfan Farhan Rijaluddin; Firdaus Ramadhan; Reza Bayu Zikrillah; Dwi Cahya Kusuma (Scripta Biologica, 2017)
The changes in the physicochemical of waters in the lake ecosystem caused by seasonal variation, anthropogenic and industrial wastes impact the gastropod community. This study aimed to determine the physicochemical parameter of waters, community structure and distribution of gastropod, and the correlation between those two in the dry and rainy seasons. We conducted this research in the lake of Situ Gintung located in Tangerang Selatan, Banten, Indonesia during the dry season (May to August 2015) and the rainy season (February to April 2016). Statistical analysis showed the physicochemical parameter of waters in both seasons has no different, while the gastropod showed a slight difference in occurrence based on the season, in which rainy season had the highest occurrence. Canonical Correspondence Analysis (CCA) suggested that gastropods occurrence were affected by the light intensity in the rainy season and the temperature in the dry season.